IMPROVING MATHEMATICAL PROBLEM-SOLVING ABILITY ON ANGLE TOPICS THROUGH DISCOVERY LEARNING ASSISTED BY SCOUT SEMAPHORE ETHNOMATHEMATICS - Abdullah Basar; Yuni Ratnasari; Eka Zuliana (Universitas Negeri Medan, 2026)
This study addresses the low mathematical problem-solving ability of Grade 5 students at SD 2 Bae, Kudus, on angle topics, evidenced by a pre-cycle class average of 35.46 and a 6.7% classical mastery rate. The objective of this research is to improve students' mathematical problem-solving ability and teacher teaching skills through a Discovery Learning model assisted by Scout semaphore ethnomathematics. The semaphore signaling system, in which each of the 26 letters (A-Z) forms a geometrically measurable angle (45°, 90°, 135°, 180°), bridges cultural scouting practice and formal mathematical concepts of angles. This Classroom Action Research (CAR) study employed the Kemmis and McTaggart cyclical model across two cycles with 15 Grade-5 students as subjects. Data were collected through Polya-based problem-solving tests, teacher teaching skill observation sheets (8 indicators, 13 items), semi-structured interviews, and documentation. Results showed significant improvement: class average increased from 35.46 (pre-cycle) to 85.0 (Cycle II); classical mastery rose from 6.7% to 93.3%, surpassing the ≥75% success indicator; and all four Polya indicators reached 'good' or 'very good' by Cycle II. Teacher teaching skills improved from 76.9% (fairly good) to 84.6% (good), exceeding the ≥79% target. These findings confirm that ethnomathematics-integrated Discovery Learning effectively develops mathematical problem-solving competence while promoting culturally responsive mathematics instruction.